2017 IFPRI audited financial statements - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
During 2017, IFPRI refreshed its insitutional strategy to scale up work on climate resilience, food industries and value chains, and urban food securit and nutrition. The Institute enjoyed continued recognition of its high-quality, rigorous work, ranking number one among agricultrual economics departments in Research Papers in Economics (RePEc) rankings. IFPRI researchers contributed to high-level policy discussions, including the World Trade Organization conference, COP23, and the G20 Agriculture Ministers meeting. IFPRI's Director General, Shenggen Gan, received the 2017 Fudan Management Excellence Award- known as the "Nobel Prize for Management" in China. This highly prestigious award recognizes individuals who have made outstanding contributions to the field of management. Other 2017 highlights included research work that informed India's national nutrition program, the lifting of a maize export ban in Malawi, and passage of a national biosafety bill in Uganda, as well as progress toward Africa's agricultural development goals.